THE ROLE OF COUNSELING IN IMPROVING STUDENTS' MOTIVATION TO LEARN - Halif Ilham Syahputra Azhari (Yayasan Amanah Nur Aman, 2026)
This study aims to analyze the role of Guidance and Counseling (BK) teachers in addressing student learning motivation issues in schools. Learning motivation is a key factor influencing students’ academic achievement and participation in the learning process. However, many students still experience low learning motivation due to academic pressure, lack of self-confidence, family problems, and environmental influences. This study employs a descriptive qualitative approach through observation and interviews. The results indicate that guidance and counseling teachers play a vital role in providing guidance, emotional support, motivation, and counseling services to students to enhance their enthusiasm for learning. Additionally, collaboration among teachers, parents, and school administrators significantly contributes to supporting students’ learning motivation. This study underscores the importance of counseling services in creating a learning environment that supports students’ academic and emotional development.